Spatiotemporal characteristics of the dam-break induced surge pressure on a vertical wall. Issue 4 (1st October 2020) - Shen, Jia; Wei, Lusong; Wu, Danhong; Liu, Haijiang; Huangfu, Jiangtao
ABSTRACT: In this study, the impact process on a vertical wall due to the dam-break-induced surge was investigated experimentally. The entire surge impact process is classified into three stages, i.e. the initial impact stage, the reflected stage, and the second impact stage. Meanwhile, the wall is vertically divided into the bottom impact zone and the upper outer zone. In the initial impact stage, the upper turbulent and the lower steady splash-ups occur. Only the steady splash-ups induce horizontal pressures on the wall. In the reflected stage, a pressure oscillation occurs, which can be estimated using the pressure oscillation model. Pressure distribution in the impact zone has a large vertical gradient only in the initial impact stage. Surge force exerting on the bottom impact zone remains large in the entire process, whereas surge force in the outer zone is important only in the reflected stage. The maximum total force is equally contributed by the impact and outer zone components. A modified water wedge model was proposed, which predicts the pressure-rising process reasonably. The solid body assumption is suitable only for the turbulent splash-ups in the outer zone, which however is oversimplified for the steady splash-ups movement in the impact zone.